Facilitators and Barriers Affecting Implementation of Neonatal Palliative Care by Nurses in Mainland China - Zhong, Yajing; Black, Beth Perry; Kain, Victoria J.; Song, Yang (Frontiers in Pediatrics, 2022)
Neonatal nurses in mainland China encounter various challenges when it comes to delivering palliative care to neonates. The aim of this study was to determine the barriers and facilitators of neonatal nurses' attitudes to palliative care for neonates in mainland China. A simplified Chinese version of the Neonatal Palliative Care Attitude Scale was piloted, administered, and analyzed using survey methods. Nurses in neonatal intensive care units in mainland China regardless of experience in the field were invited to take part in. Over a five-month period in 2019, we surveyed neonatal nurses from 40 hospitals in five provinces of China. The response rate was 92.5% (N=550). This study identified eight facilitators and four barriers to neonatal palliative care implementation. In terms of nurses' attitudes on providing palliative care, younger and older nurses were more positive, whereas middle-aged nurses were less so. Nurses' emotional well-being was rarely impacted by neonatal death. They considered neonatal palliative care, particularly pain management, to be just as important as curative treatment. Parents were invited to participate in decision-making by nurses. Nurses reported having access to professional counselling and talking about their concerns with other healthcare professionals. The following barriers to neonatal palliative care were identified in this study that were not observed in the original English version scale research in 2009: a lack of clinicians, time, clinical skills, systematic education, neonatal palliative care experience, and social acceptance. Future research is required to investigate each barrier in order to improve the implementation of neonatal palliative care in mainland China.